Relation between mast cells concentration and serotonin expression in chagasic megacolon development. (March 2017) - Freitas, M. A. R.; Segatto, N.; Tischler, N.; de Oliveira, E. C.; Brehmer, A.; da Silveira, A. B. M.
Summary: Chagas' disease is still reaching about 10 million people in the world. In South America, one of the most severe forms of this disease is the megacolon, characterized by severe constipation, dilated sigmoid colon and rectum and severe malnutrition. Previous data suggested that mast cells and serotonin (5‐hydroxytryptamine [5‐HT]) expression could be involved in intestinal homeostasis control, avoiding the chagasic megacolon development. The aim at this study was to characterize the presence of mast cells and expression of serotonin in chagasic patients with and without megacolon and evaluate the relation between mast cells, serotonin and megacolon development. Our results demonstrated that patients without megacolon feature a large amount of serotonin and few mast cells, while patients with megacolon feature low serotonin expression and a lot of mast cells. We believe that serotonin may be involved in the inflammatory process control, triggered by mast cells, and the presence of this substance in large quantities of the intestine could represent a mechanism of megacolon prevention.